Advances in Technical Diagnostics Proceedings of the 6th International Congress on Technical Diagnostics, ICTD2016, 12 - 16 September 2016, Gliwice, Poland - Timofiejczuk, Anna.; Łazarz, Bogusław Edward; Chaari, Fakher; Burdzik, Rafał; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book provides readers with an overview of recent theories and methods for machinery diagnostics applied to machinery maintenance. Each chapter, accepted after a rigorous peer-review process, reports on a selected, original piece of work discussed at the International Congress on Technical Diagnostics, ICTD2016, held on September 12 - 16, 2016, in Gliwice, Poland. The book covers a broad range of topics, including machines operating in non-stationary conditions, and examples from different industrial fields of mechanical, civil, computer and electronic engineering as well as the medical, food, automotive, and mining industries. By presenting state-of-the-art diagnostic solutions and discussing important industrial issues the book offers a valuable resource to both academics and professionals as well as a bridge to facilitate communication and collaboration between the two groups.
From the Content: Maintenance of Gas Turbine Based on Vibration Analysis and Measurement: Gas Compression Station Investigation -- Gas Turbine Supervision System Based on Fuzzy Reliability and Availability -- Propagation of Structural Vibrations and Pressure Waves in the Hydropower Turbines.
Keywords: Machinery; Multibody systems; Vibration; Mechanics, Applied; Biomedical engineering; Machinery and Machine Elements; Multibody Systems and Mechanical Vibrations; Biomedical Engineering and Bioengineering